Targeting chemoresistance and mitochondria-dependent metabolic reprogramming in acute myeloid leukemia - Feng, Lili; Zhang, Philip Y.; Gao, Wenda; Yu, Jinming; Robson, Simon C. (Frontiers in Oncology, 2023)
Chemoresistance often complicates the management of cancer, as noted in the instance of acute myeloid leukemia (AML). Mitochondrial function is considered important for the viability of AML blasts and appears to also modulate chemoresistance. As mitochondrial metabolism is aberrant in AML, any distinct pathways could be directly targeted to impact both cell viability and chemoresistance. Therefore, identifying and targeting those precise rogue elements of mitochondrial metabolism could be a valid therapeutic strategy in leukemia. Here, we review the evidence for abnormalities in mitochondria metabolic processes in AML cells, that likely impact chemoresistance. We further address several therapeutic approaches targeting isocitrate dehydrogenase 2 (IDH2), CD39, nicotinamide phosphoribosyl transferase (NAMPT), electron transport chain (ETC) complex in AML and also consider the roles of mesenchymal stromal cells. We propose the term "mitotherapy" to collectively refer to such regimens that attempt to override mitochondria-mediated metabolic reprogramming, as used by cancer cells. Mounting evidence suggests that mitotherapy could provide a complementary strategy to overcome chemoresistance in liquid cancers, as well as in solid tumors.